2005
DOI: 10.1074/jbc.c400496200
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Cysteine Sulfinic Acid by Sulfiredoxin Is Specific to 2-Cys Peroxiredoxins

Abstract: Cysteine residues of certain peroxiredoxins (Prxs) undergo reversible oxidation to sulfinic acid (Cys-SO 2 H) and the reduction reaction is catalyzed by sulfiredoxin (Srx). Specific Cys residues of various other proteins are also oxidized to sulfinic acid, suggesting that formation of Cys-SO 2 H might be a novel posttranslational modification that contributes to regulation of protein function. To examine the susceptibility of sulfinic forms of proteins to reduction by Srx, we prepared such forms of all six mam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
228
2
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 291 publications
(239 citation statements)
references
References 33 publications
7
228
2
2
Order By: Relevance
“…Several lines of evidence support the selective binding of typical 2-Cys Prxs by Srx (Woo et al, 2005): (i) the GST-Srx fusion protein can bind the reduced and oxidized forms of PrxI-IV from HeLa cells with and without H 2 O 2 treatment, but not the atypical 2-Cys PrxV or the 1-Cys PrxVI; (ii) reduced hPrxI can compete for hyperoxidized hPrxI in the reductase antibody assay; (iii) a yeast two-hybrid screen indicated interactions only between Srx and PrxI-IV; and (iv) overexpression of Srx in A549 cells reduces the levels of hyperoxidzed PrxI-IV upon H 2 O 2 treatment, but not the other Prxs or glyceraldehyde-3-phosphate dehydrogenase (GAPDH). Activity analyses using recombinant PrxI-6 have further confirmed that only the typical 2-Cys PrxI-IV are reduced.…”
Section: Substrate Specificity and Mutational Analysismentioning
confidence: 96%
See 3 more Smart Citations
“…Several lines of evidence support the selective binding of typical 2-Cys Prxs by Srx (Woo et al, 2005): (i) the GST-Srx fusion protein can bind the reduced and oxidized forms of PrxI-IV from HeLa cells with and without H 2 O 2 treatment, but not the atypical 2-Cys PrxV or the 1-Cys PrxVI; (ii) reduced hPrxI can compete for hyperoxidized hPrxI in the reductase antibody assay; (iii) a yeast two-hybrid screen indicated interactions only between Srx and PrxI-IV; and (iv) overexpression of Srx in A549 cells reduces the levels of hyperoxidzed PrxI-IV upon H 2 O 2 treatment, but not the other Prxs or glyceraldehyde-3-phosphate dehydrogenase (GAPDH). Activity analyses using recombinant PrxI-6 have further confirmed that only the typical 2-Cys PrxI-IV are reduced.…”
Section: Substrate Specificity and Mutational Analysismentioning
confidence: 96%
“…At this time no further characterization of the sulfinic acid reductase activity of sestrins has been reported. Data presented from the Rhee laboratory in section 6.2 has shown that Srx is specific for typical 2-Cys Prxs (Woo et al, 2005).…”
Section: Discovery and Initial Characterization Of Sestrinmentioning
confidence: 99%
See 2 more Smart Citations
“…Cysteine sulfinic acid is generally thought to represent an irreversible oxidative product of protein thiols that that can progress to the sulfonic acid oxidation state. However, recent data have documented an exception, showing that the sulfinic acid moiety in 2-Cys peroxiredoxins in cells under oxidative stress can be reduced by two ATP-dependent reductases, sulfiredoxin and sestrin [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%